Return and volatility spillovers among the East Asian equity markets - Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2009)
This article examines the extent of contagion and interdependence across the East Asian equity markets since early 1990s and compares the ongoing crisis with earlier episodes. Using the forecast error variance decomposition from a vector autoregression, we derive return and volatility spillover indices over the rolling sub-sample windows. We show that there is substantial difference between the behavior of the East Asian return and volatility spillover indices over time. While the return spillover index reveals increased integration among the East Asian equity markets, the volatility spillover index experiences significant bursts during major market crises, including the East Asian crisis. The fact that both return and volatility spillover indices reached their respective peaks during the current global financial crisis attests to the severity of the current episode.
Keywords: G1; F3; 330; Stock returns; Volatility; Spillovers; Vector autoregression; Variance decomposition; Kapitalertrag; Volatilität; Spillover-Effekt; Dekompositionsverfahren; Schätzung; Ostasien